Change of solvent proportion effect on pilot plan scale extraction of alginate from Sargassum sp. Issue 1 (March 2020) - Kusumawati, R; Basmal, J; Utomo, B S B
Abstract: Alginate extraction from Sargassum sp. pilot plant scale has been done. The extraction technique used refers to the modification of laboratory scale extraction techniques using acidic methods. On a scale of 1 kg of raw material, modification of the extraction technique was carried out on the proportion of bleaching material, sodium hypochlorite (NaOCl), which was originally 4% (v/v) to 2% (v/v). On a scale of 3 kg of raw material, modifications are made to the volume of water for extraction, which was originally 30 times the weight of the raw material to 20 times the weight of the raw material. On a scale of 10 kg of raw material, modifications are made to the ratio of water binder, iso propyl alcohol (IPA), which was originally 8 times the weight of the raw material to 3 times the weight of the raw material. The results of the study show that modification of the solvent carried out at each production scale causes an increase in yield (17.97, 19.79, and 22.67%) and a decrease in viscosity (128.43, 55.03, and 40.27 cPs).